The benefits of an employee-friendly company on job attitudes and health of employees: findings from matched employer-employee data - Herr, Raphael; Brokmeier, Luisa Leonie; Fischer, Joachim E.; Mauss, Daniel (International journal of environmental research and public health, 2022)
Background: This study explored the association of an employee-friendly work environment with employees’ job attitudes (engagement, commitment, turnover intentions, and job satisfaction), and health (mental and general health), applying matched employer-employee data. Methods: The German Linked Personnel Panel (LPP; n = 14,182) survey simultaneously captures the data of employees and the human resources (HR) management of companies. A two-step cluster analysis of 16 items of the HR valuation identified relatively more- and less-employee-friendly companies (EFCs). Logistic regressions tested differences between these companies in the assessment of job attitudes and health of their employees. Results: Compared to less-EFCS, more-EFCS had a reduced risk of poorer job attitudes and substandard health of their employees. For example, the risk for higher turnover intentions was reduced by 33% in more-EFCS (OR = 0.683, 95% C.I. = 0.626-0.723), and more-EFCS had an 18% reduced chance of poor mental health reporting of their employees (OR = 0.822, 95% C.I. = 0.758-0.892). Conclusions: More-EFCS have more motivated and healthier employees. The most distinct factors for more-EFCS were: the existence of development plans for employees, opportunities for advancement and development, and personnel development measures.
Dieser Artikel gehört zum Special issue: Workplace health, wellbeing and productivity
Gesehen am 23.10.2023